On the tribo-dynamic interactions between piston skirt-liner system and pin assembly in a gasoline engine. (December 2021) - Fang, Congcong; Meng, Xianghui; Zhou, Wei; Huang, Hongchen
Highlights: A model couples piston skirt-liner system and floating pin assembly is developed. Tribo-dynamic interaction mechanisms between the two friction pairs are revealed. Effects of design parameters including piston pin clearance and offset are probed. Friction torque on pin visibly affects piston tribo-dynamic behavior near the FTDC. Piston is more sensitive to pin offset than pin assembly in tribo-dynamic behavior. Abstract: Piston Skirt-Liner (PSL) system and Piston Pin Bearing (PPB), two key friction pairs in piston-assembly, interact with each other via impact and friction when transmitting the combustion load to crank train. Literature reporting such an interaction behavior in terms of tribology and dynamics is still rare, due to the complexity in a systematic modeling way. This paper proposed an efficient numerical model that fully couples these two friction pairs to investigate tribo-dynamic interactions between them. The model is built by coupling Reynolds-based mixed lubrication models for the friction pairs with Lagrange multibody motion equations for the piston-connecting rod-crank mechanism. Coupling effects between the piston skirt-liner system and the pin assembly are explored by comparing the cases contain the two friction pairs and one of them. Based on the above analyses, some design parameters including pin assembly clearance and pin offset, are further studied to disclose their influences on the tribo-dynamic performance of these two friction pairs. This work has a guiding significance for the systematic design of piston-assembly aiming to improve the dynamic property, economical efficiency and environmental-friendliness of engines.